5(2x-11)=3x+9

Simple and best practice solution for 5(2x-11)=3x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-11)=3x+9 equation:


Simplifying
5(2x + -11) = 3x + 9

Reorder the terms:
5(-11 + 2x) = 3x + 9
(-11 * 5 + 2x * 5) = 3x + 9
(-55 + 10x) = 3x + 9

Reorder the terms:
-55 + 10x = 9 + 3x

Solving
-55 + 10x = 9 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-55 + 10x + -3x = 9 + 3x + -3x

Combine like terms: 10x + -3x = 7x
-55 + 7x = 9 + 3x + -3x

Combine like terms: 3x + -3x = 0
-55 + 7x = 9 + 0
-55 + 7x = 9

Add '55' to each side of the equation.
-55 + 55 + 7x = 9 + 55

Combine like terms: -55 + 55 = 0
0 + 7x = 9 + 55
7x = 9 + 55

Combine like terms: 9 + 55 = 64
7x = 64

Divide each side by '7'.
x = 9.142857143

Simplifying
x = 9.142857143

See similar equations:

| 3/5.22 | | 4(x+1)-2(-x-1)=0 | | 12+10=10+12 | | 6x-30+1=0 | | 3-7(-x+5)=2x+5 | | 40(x)+60(y)=1700 | | 8(x-1)-2(3x+4)=0 | | 4x^2+9y^2-8x-54y-59=0 | | ln(3x+2)-ln(2)=1 | | ln(x^3+x^2-2)=ln(x-1)(x^2-1) | | X+2x-1=11 | | 10x-24=4x | | x^2=8-9x | | 3.25n+2=3n+6 | | -3x+6=-6x | | 5y+11=(3y+7) | | 4w(7w+3)=0 | | -2x+9x+5=0 | | 4x^4+36x^3= | | (t+2)(6t+1)=0 | | 7.5x-2.5=20.0 | | 11x+37=90 | | 36x4/9= | | 4(3x-2)+3x-7=0 | | 22-30x-1=-63 | | 4ab=16 | | (2y+2)(2y-4)=0 | | 15=0.6(10+n) | | 4(6z-1)-2(z+6)=9(z+1) | | 7p^2-54p-16=0 | | 7x+y=-28 | | 9x^3+6x^2-6x-2=0 |

Equations solver categories